Under-ice convection dynamics in a boreal lake. Issue 2 (3rd April 2019) - Bouffard, Damien; Zdorovennova, Galina; Bogdanov, Sergey; Efremova, Tatyana; Lavanchy, Sébastien; Palshin, Nikolay; Terzhevik, Arkady; Vinnå, Love Råman; Volkov, Sergey; Wüest, Alfred; Zdorovennov, Roman; Ulloa, Hugo N.
ABSTRACT: We investigated radiatively driven under-ice convection in Lake Onego (Russia) during 3 consecutive late winters. In ice-covered lakes, where the temperature of water is below the temperature of maximum density, radiatively driven heating in the upper water column induces unstable density distributions leading to gravitational convection. In this work, we quantified the key parameters to characterise the radiatively driven under-ice convection: (1) the effective buoyancy flux, B ∗ (driver), and its vertical distribution; (2) the convective mixed-layer thickness, h C M L (depth scale); and (3) the convective velocity, w ∗ (kinematic scale). We compared analytical w ∗ scaling estimates to in situ observations from high-resolution acoustic Doppler current profilers. The results show a robust correlation between w ∗ and the direct observations, except during the onset and decay of the solar radiation. Our results highlight the importance of accurately defining the upper limit of h CML in highly turbid water and the need for spectrally resolving solar radiation measurements and their attenuation for accurate B ∗ estimates. Uncertainties in the different parameters were also investigated. We finally examined the implications of under-ice convection for the growth rate of nonmotile phytoplankton and provide a simple heuristic model as a function of easily measurable parameters.